Nutrient intake and cerebral metabolism in healthy middle-aged adults: Implications for cognitive aging. (14th September 2017) - Oleson, Stephanie; Gonzales, Mitzi M.; Tarumi, Takashi; Davis, Jaimie N.; Cassill, Carolyn K.; Tanaka, Hirofumi; Haley, Andreana P.
Abstract : Objectives : Growing evidence suggests dietary factors influence cognition, but the effects of nutrient intake on cerebral metabolism in adults are currently unknown. The present study investigated the relationship between major macronutrient intake (fat, carbohydrate, and protein) and cerebral neurochemical profiles in middle-aged adults. Methods : Thirty-six adults recorded dietary intake for 3 days prior to completing cognitive testing and a proton magnetic resonance spectroscopy ( 1 H-MRS) scan. 1 H-MRS of occipitoparietal gray matter was used to assess glutamate (Glu), N -acetyl-aspartate (NAA), choline (Cho), and myo- inositol (mI) relative to creatine (Cr) levels. Results : Regression analyses revealed that high intake of polyunsaturated fatty acids (PUFAs) was associated with lower cerebral Glu/Cr ( P  = 0.005), and high intake of saturated fat (SFA) was associated with poorer memory function ( P  = 0.030) independent of age, sex, education, estimated intelligence, total caloric intake, and body mass index. Discussion : In midlife, greater PUFA intake (ω-3 and ω-6) may be associated with lower cerebral glutamate, potentially indicating more efficient cellular reuptake of glutamate. SFA intake, on the other hand, was linked with poorer memory performance. These results suggest that dietary fat intake modification may be an important intervention target for the prevention of cognitive decline.